Pravljične pošasti in pošastno v oglasihFairy Tale Monsters and the Monstrous in Advertising - Klaus, Simona (Studia mythologica Slavica, 2014)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">In folklore, evil has always been represented by monsters in various shapes and sizes. Through cultures, the demonic world has been the fearsome counterpart of the good, the two worlds coexisting in a constant struggle. In folklore, many fairy tales, tales and other narratives speak of this battle between good and bad. It does not come as a surprise that this motif also appears in advertisements, which shape our everyday way of life. This article addresses the issue of how advertisements use monsters to represent various fears, i.e. disease or bacteria, and the advertised product as an instant, magic means to overcome it.